Islamic Education for Disabilities: Exploring Psychological Approaches through Bibliometric Analysis - Tamami, Fauziyah Qurrota Ayun; Maksum, Muhammad Nur Rochim; Rahmawati, Siti; Anwari, Afifah (Multicultural Islamic Education Review, 2024)
This study aims to determine the mapping of the development and direction of research on Islamic Education for disability, reviewing on Psychological through bibliometric analysis taken from several articles indexed by the Scopus database, the results of data found in tiers from 2020 to 2024 to find relevant gaps. The data obtained is then analyzed using software in the form of R/R-Studio, VOSViewer, Microsoft Excel to find keywords, stimulant document citations. 431 papers were located by researchers that satisfied the predetermined criteria for subject, function, and size. This study’s findings indicate a yearly increase rate. The collected articles are examined based on the number of research published annually and the science field. The scope of the bibliometric analysis was restricted to data from Scopus. This study’s shortcoming is that it only uses data sets or meta data for publications that Scopus has indexed. This study offers suggestions for futhuer research as well as a concise summary of the material available to scholars studing Islamic Education for Disabilities Psychological Review.